Anatomo-radiological correlation using 18-FDG-PET in abdominal sepsis model in rats. A preliminary study - Azevedo,Ítalo Medeiros (2017)
Abstract Purpose: To examine a correlation of micro-PET images with photographic images of the digestive organs in abdominal sepsis model. Methods: Male Wistar rats weighing 265±18g were used. Abdominal sepsis was induced by ligature and cecal puncture. Micro-PET Images from abdominal cavity septic foci were obtained using 18-Fluoro-deoxyglucose, looking for a correlation with photographic images of abdominal cavity organs. Pearson's correlation test was used. Results: The mean standard uptake values (SUV) and lesion areas were 2.58±0.63SUVbwg/ml and 546.87±300.95mm2, respectively. There was a strong positive correlation between the two variables (r=0.863, p=0.137), which resulted in a coefficient of determination r2?0.75, meaning that 75% of SUV variation is explained by the lesion areas of digestive organs. Conclusion: Micro-PET allows high throughput assessment of lesion count and volume in pre-clinical rat model of CPL abdominal sepsis.